2015
DOI: 10.1002/bin.1420
|View full text |Cite
|
Sign up to set email alerts
|

Review and Discussion of Strategies to Address Low Trainer‐to‐Staff Ratios

Abstract: Researchers have developed an array of highly adaptable intervention packages with well-documented efficacy for staff and teacher training. As indicated by Parsons, Rollyson, and Reid (2012) in their article on best practices in staff training, behavior analysts must use methods that are both effective and efficient given the limited resources of many human service settings (e.g., low trainer-to-staff ratios). The purpose of this paper is to summarize research on practical innovations for staff and teacher tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 61 publications
1
16
0
Order By: Relevance
“…Behavior analysts are responsible for training direct-service interventionists (i.e., teachers, parents, clinicians) in behavior analytic practices for the individuals they serve (e.g., children with developmental disabilities; Behavior Analyst Certification Board®, 2015). Recent research has focused on innovative training approaches to train service providers via distance training or “telehealth” (Karsten, Axe, & Mann, 2015; Neely, Rispoli, Gerow, Hong, & Hagan-Burke, 2017). Telehealth technologies can allow specialists to maximize resources by providing training to a greater number of people with inexpensive equipment (Wacker et al, 2013).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Behavior analysts are responsible for training direct-service interventionists (i.e., teachers, parents, clinicians) in behavior analytic practices for the individuals they serve (e.g., children with developmental disabilities; Behavior Analyst Certification Board®, 2015). Recent research has focused on innovative training approaches to train service providers via distance training or “telehealth” (Karsten, Axe, & Mann, 2015; Neely, Rispoli, Gerow, Hong, & Hagan-Burke, 2017). Telehealth technologies can allow specialists to maximize resources by providing training to a greater number of people with inexpensive equipment (Wacker et al, 2013).…”
mentioning
confidence: 99%
“…Performance feedback is a critical component of training with immediate performance feedback demonstrating greater gains versus delayed feedback. As a modification, video-based performance feedback involves an interventionist filming a session with a client and receiving performance feedback from their trainer at a later time based on the recorded session (Karsten et al, 2015; Neely et al, 2016). Video-based feedback can address time barriers by allow for flexibility in training times (Karsten et al, 2015).…”
mentioning
confidence: 99%
“…Substantial research has shown BST to be effective at increasing the fidelity of implementation of intervention procedures by teachers, especially preservice teachers (Kranak et al, 2018). However, BST is resource intensive and often requires the presence of a skilled trainer (Karsten, Axe, & Mann, 2015). Given the shortage in skilled special education teachers who can provide evidence‐based practices to children with ASD in China (Fan & Hu, 2015), BST may not be the most feasible approach to staff training in mainland China.…”
Section: Introductionmentioning
confidence: 99%
“…A promising technique that requires fewer staff is video modeling (VM). VM procedures, which involve showing the learner a video depicting a trained individual engaging in the target behavior either in a role‐play or real life scenario (Karsten et al, 2015), may circumvent the need for skilled staff to be present. VM has been successfully used to teach staff who work with children with ASD specific behavioral intervention strategies like discrete trial instruction (Catania, Almeida, Constant, & Reed, 2009), preference assessments (Rosales, Gongola, & Homlitas, 2015), functional analysis (Moore & Fisher, 2007), time out procedures (Slider, Noell, & William, 2006), motor imitation procedures (Lin, Nuzzolo, & Alonso‐Alvarez, 2016), problem‐solving intervention (Collins, Higbee, & Salzberg, 2009), problem behavior treatment (DiGennaro‐Reed, Codding, Catania, & Maguire, 2010), and prompting strategies (Giannakakos, Vladescu, Kisamore, & Reeve, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation